Bacillus amyloliquefaciens GB03 augmented tall fescue growth by regulating phytohormone and nutrient homeostasis under nitrogen deficiency - Wang, Qian; Ou, Er-Ling; Wang, Pu-Chang; Chen, Ying; Wang, Zi-Yuan; Wang, Zhi-Wei; Fang, Xiang-Wen; Zhang, Jin-Lin (Frontiers in Plant Science, 2022)
Nitrogen is an important nutrient for plant growth and development. In ecologically fragile areas, facing to the contradiction between the limited effectiveness of natural environmental nitrogen and the pollution of increasing nitrogen fertilizer, soil microorganisms have been used to solve this conflict. Bacillus amyloliquefaciens GB03 has been shown to confer growth promotion and abiotic stress tolerance in Arabidopsis thaliana. This study provided a new insight into the role of a plant growth-promoting rhizobacteria Bacillus amyloliquefaciens GB03 as initiators of defense nitrogen deficiency in non-leguminous grass tall fescue (Festuca arundinacea). Two-week-old seedlings of tall fescue were grown with or without GB03 for another 4 weeks under total nitrogen (TN-3.75 mM NO3-) or low nitrogen (LN-0.25 mM NO3-) treatment. Growth parameters, chlorophyll content, endogenous total nitrogen and total phosphorus contents and phytohormones contents, including auxin indole-3-actetic acid (IAA), cytokinin (CK), gibberellic acid (GA) and abscisic acid (ABA) were determined at the harvest time of plants. Tall fescue grown in GB03-inoculated soil were more robust than non-inoculated controls with respects to plant height, root length, plant biomass, chlorophyll concentration and nutrients (total nitrogen and total phosphorus) contents under TN, in parallel, the contents of IAA was increased whereas the contents of CK and ABA were decreased significantly. The similar results about GB03 promotion growth were observed under LN except growth and nutrient accumulation in roots. The results presented here showed, for the first time, that GB03 played a crucial role in mediating NO3--dependent regulation of tall fescue growth and development by facilitating chlorophyll, N, P and IAA contents, as well as repressing CK and ABA contents. It was noteworthy that compared with the growth promotion effect under total nitrogen level, GB03 increased IAA content by more than 80%, and inhibited CK and ABA contents by nearly 70% under low nitrogen level, which provided the mechanism underlying of soil bacteria in improving the resistance of nitrogen deficiency stress in non-nitrogen-fixing species.